Feminist Linguistic Analysis on Selected Poems of Language Discipline - Lopez, Kyth Guenevere; Dela Torre, Christine M.; R. Eugenio, Chaaziel; Monteza, Ana Mae M. (J-Lalite: Journal of English Studies, 2024)
This study focuses on analyzing the eight selected poems in language discipline, particularly in the context of women’s objectification. The objective of this study is communication patterns of women's objectification from Sara Mills' Feminist Stylistics. This exploration applied a content analysis approach and Fredrickson and Roberts’ objectification theory. The major findings reveal that women are expected to be obedient and do household chores, are being reduced by their body parts for men’s sexual desires, and are used to objectify them. Further, women are treated based on their clothes, as what they wear highlights their sexuality and beauty, amplifying the notion of women being reduced to sexual objects rather than treating them as a person with identities. More distressing is the revelation of women being labeled with different names if they do not conform to society's expectations, which emphasized women as being passive and unwilling to receive the actions from men. Finally, this study is highly significant for language learners as it could help them to be more adept in analyzing literary texts while enhancing their critical thinking skills on language and gender representation, aligning with Sustainable Development Goal No. 5 on Gender Equality, mainstreaming eradication of any forms of discrimination